Упростите выражение #80

Упростите выражение #80
Гость
Ответ(ы) на вопрос:
Гость
пользуйся на здоровье
Гость
[latex](\frac{m-3}{m^{2}-4m+3 } - \frac{2m}{ m^{2}-1 } ): \frac{1}{5m+5}=  [/latex] [latex](\frac{m-3}{(m-3)(m-1)} - \frac{2m}{ (m-1)(m+1) } ): \frac{1}{5m+5}= [/latex] [latex](\frac{1}{m-1} - \frac{2m}{ (m-1)(m+1) } )* \frac{5(m+1)}{1}=[/latex] [latex]\frac{m+1-2m}{(m-1)(m+1) } * \frac{5(m+1)}{1}=[/latex] [latex]\frac{-(m-1)}{(m-1)} * \frac{5}{1}=[/latex] [latex] \frac{5*(-1)}{1} = -5[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы